Magnetic, electronic and optical properties of different graphene, BN and BC2N nanoribbons. (April 2017) - Guerra, T.; Leite, L.; Azevedo, S.; de Lima Bernardo, B.
Abstract: Graphene nanoribbons are predicted to be essential components in future nanoelectronics. The size, edge type, form, arrangement of atoms and width of nanoribbons drastically change their properties. However, magnetic, electronic and optical properties of armchair, chevron and sawtooth of graphene, BN and BC2 N nanoribbons are not fully understood so far. Here, we make use of first-principles calculations based on the density functional theory (DFT) to investigate the structural, magnetic, electronic and optical properties of nanoribbons of graphene, boron nitride and BC2 N with armchair edge, chevron-type and sawtooth forms. The lowest formation energies were found for the armchair and chevron nanoribbons of graphene and boron nitride. We have shown that the imbalance of carbon atoms between different sublattices generates a net magnetic moment. Chevron-type nanoribbons of BC2 N and graphene showed a band gap comparable with silicon, and a high light absorption in the visible spectrum when compared to the other configurations. Highlights: It is obtained the optical and conductivity properties. It is shown that such nanoribbons can be used for applications in photovoltaic cells. The nanoribbons display magnetism that can be described by Lib's theorem.